Saliva-Based Biosensors: Noninvasive Monitoring Tool for Clinical Diagnostics. (8th September 2014) - Malon, Radha S. P.; Sadir, Sahba; Balakrishnan, Malarvili; Córcoles, Emma P.
Abstract : Saliva is increasingly recognised as an attractive diagnostic fluid. The presence of various disease signalling salivary biomarkers that accurately reflect normal and disease states in humans and the sampling benefits compared to blood sampling are some of the reasons for this recognition. This explains the burgeoning research field in assay developments and technological advancements for the detection of various salivary biomarkers to improve clinical diagnosis, management, and treatment. This paper reviews the significance of salivary biomarkers for clinical diagnosis and therapeutic applications, with focus on the technologies and biosensing platforms that have been reported for screening these biomarkers.